Analysis of Marine Products Export from India using Markov-Chain Analysis - Chandrasekar, V.; Paramasivam, P.; Jayanthi, C.; Sathy, R.; Gopal, Nikita; Mani, K. (Fishery Technology, 2020)
The present study analyses the changing pattern ofmarine product exports from India to seven regions/countries such as Japan, USA, European Union(E.U), China, South East Asia (SEA), Middle East(ME) and others, during two decades from 1995 to2015. The average growth rate of marine seafoodexport in relation to quantity and value for the twodecades was 6.78 and 12.5% respectively. Frozenshrimp export quantity had nearly 40% share in thetotal export basket. Instability in value was higherthan the quantity of export, out of which frozenshrimp price instability was nearly 60%. UsingMarkov Chain Analysis, it was observed thatEuropean Union was having higher probability ofretention (0.82) compared to the other regions. In thefirst decade Japan was the major importer withhigher probability of retention which reduced from0.91 to 0.56 during the second decade with a gainby European Union (0.87) in the same decade.Â